Growth of free-floating aquatic macrophytes in different concentrations of nutrients - Henry-Silva, Gustavo G.; Camargo, Antonio Fernando Monteiro [UNESP]; Pezzato, Maura M. (Springer, 2008)
The objective of the study was to evaluate the effect of different concentrations of nitrogen and phosphorus on the growth of the free-floating aquatic macrophytes Eichhornia crassipes, Pistia stratiotes, and Salvinia molesta. The plants were cultured in 2,000-l outdoor concrete tanks. Triplicate tanks, with a continuous flow of effluent from culture ponds containing Nile tilapia, were used for each plant type (n = 3). The plant material was collected monthly from 0.25 m(2) floating quadrats, at the two ends of the tanks (higher nutrient concentrations near the inflow and lower nutrient concentrations near the outflow). In low nutrient concentrations, the maximum relative growth rates (RGRs) for E. crassipes (0.016/day) and P. stratiotes (0.016/day) were significantly lower (P <= 0.05) than for S. molesta (0.029/day). There were no significant differences between the RGRs of S. molesta in the different nutrient concentrations. Eichhornia crassipes and P. stratiotes had their growth limited by nitrogen and phosphorus concentrations. The increase in plant density during the experiment probably also affected the growth of these species. In this context, E. crassipes and P. stratiotes can cause problems in nutrient-rich waterbodies, but under these experimental conditions their growth was limited by nitrogen and/or phosphorus concentrations. The growth of S. molesta was not influenced by the different nutrient concentrations.
Keywords: Eichhornia crassipes; Pistia stratiotes; Salvinia molesta; relative growth rate; nitrogen; phosphorus